The Role of AI in Marketing Strategies: Employee Perceptions Towards Business Performance-A Case Study (Architecture Image Studies, 2026)
This study aims to understand how AI plays a part in developing marketing strategies and boosting the performance of the Malaysian IT services sector, mainly from employees’ point of view. It is very important for managers to consider how AI affects their employees as these tools start to play a bigger role in business activities. With a quantitative case study, we collected information from 351 IT specialists in a top IT firm located in Selangor. AI applications were measured against business performance through the process of multiple regression analysis. It was observed that AI Personalization Techniques have the greatest influence on customer satisfaction (β = 0.564, p < 0.001), then AI-Powered Chatbots (β = 0.156, p = 0.012) and AI-Driven Marketing Automation (β = 0.123, p = 0.018). These AI strategies share responsibility for 61.8% of the variation in business performance (R² is equal to 0.618). Based on the findings, AI tools make tasks faster and help generate interactions with customers, which helps businesses become more competitive. This research points out that IT service providers wishing to connect AI effectively should keep training employees, foster unity within the organization, and use innovative approaches in marketing.